Child Labor in Farming Households in the Niger Delta Region of Nigeria. Issue 1 (March 2020) - Ofuoku, Albert Ukaro; Ovharhe, Oghenero Joseph; Agbamu, Joseph Unuetara
Child labor is a major issue in many parts of the Global South. This study was conducted in the Niger Delta region of Nigeria to examine the level of involvement of children in arable farming activities. Three states in the region were selected for the study, and arable farming households were randomly selected from these states. Out of the selected farming households, 362 children (6–17 years of age) were interviewed. It was found that children were highly involved in most of the farming activities that are considered hazardous. The reasons given by the farming household heads for the engagement of household children in farming activities included cultural, economic, and political factors. Most of the children combined schooling and farming activities. The research data showed that there was no significant relationship in the level of involvement of children in agricultural labor between the three Niger Delta states, but it showed significant difference in the nature of farming activities in which the children were involved. The implications of agricultural development are that these conditions will lead to the transmission of agricultural knowledge, technical, and social skills from generation to generation. It is recommended that (a) a compromise should be reached between schooling and the involvement of children in farming activities; (b) that children should always be made to wear protective gear when they carry out hazardous farming operations; and (c) their involvement and technical education in agricultural skills should give them a future positive interest in agriculture as a career/profession.